2019
DOI: 10.1038/s41598-019-43228-0
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates the onset of non-alcoholic fatty liver disease and affects intestinal microbiota and barrier in small intestine

Abstract: The antidiabetic drug metformin has been proposed to affect non-alcoholic fatty liver disease (NAFLD) through its effects on intestinal microbiota and barrier function. However, so far most studies focused on long-term effects and more progressed disease stages. The aim of this study was to assess in two experimental settings, if the onset of NAFLD is associated with changes of intestinal microbiota and barrier function and to determine effects of metformin herein. C57Bl/6J mice were fed a liquid control diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 59 publications
4
87
1
1
Order By: Relevance
“…Thus, the reported drug effects on the gut microbiota structure were diverse. Indeed, the anti-hyperglycemic drugs, i.e., metformin, could affect the intestinal bacterial compositions after 1 or several days of treatment (24,25,40,43), or after prolonged periods of treatments (21). For instance, Wu et al found that gut microbiota compositions after a 2-and 4-month treatment of metformin in newly T2D patients were not identical (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reported drug effects on the gut microbiota structure were diverse. Indeed, the anti-hyperglycemic drugs, i.e., metformin, could affect the intestinal bacterial compositions after 1 or several days of treatment (24,25,40,43), or after prolonged periods of treatments (21). For instance, Wu et al found that gut microbiota compositions after a 2-and 4-month treatment of metformin in newly T2D patients were not identical (21).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is strongly influenced by dietary habits [ 362 ], smoking [ 363 ], ethanol intake [ 364 ], drugs (i.e., antibiotics [ 255 , 349 , 365 , 366 , 367 ], liraglutide [ 368 ], metformin [ 369 ], curcumin [ 370 ], and environmental pollutants (i.e., heavy metals, persistent organic pollutants, volatile organic compounds, pesticides [ 62 , 371 , 372 , 373 , 374 ]).…”
Section: The Microbiota As a Target Of Environmental Factors Involmentioning
confidence: 99%
“…In a different animal model (C57Bl/6J mice fed fat-, fructose-, and cholesterol-rich diet), protective effects were also noticed following metformin administration in terms of changed composition of gut microbiota and integrity of the intestinal barrier [ 369 ].…”
Section: The Microbiota As a Target Of Environmental Factors Involmentioning
confidence: 99%
“…Metformin is the first-line drug in the management of T2DM. Despite the fact that its main action is to improve insulin sensitivity, metformin has not shown histology improvement of steatosis [51], although recently, it has shown to prevent the development of NAFLD in a mice model [52]. Its use, together with pioglitazone or liraglutide, is recommended in the treatment of NAFLD due to its recognized effect on glycemic control [8] and in relation to the associated weight loss [31] [32].…”
Section: Other Antidiabetic Agentsmentioning
confidence: 99%